The Islamic Financial Services Act, 2013: Malaysia’s model framework for Shariah-compliance and stability - Yussof, Sheila Ainon (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2013)
Malaysia is said to have created legal history by introducing the world’s first comprehensive legal framework for its Islamic Finance Industry through the pro-active approach of its central regulator (Central Bank of Malaysia, or the CBM) and government-driven Economic Transformation (ETP) Policy. This piece of legislation was crafted by regulators, policy makers and legal drafters to enforce Shariah compliance in a move towards greater financial stability. Factors such as changing demographics and increased growth of Shariah-conscious consumers worldwide, the increasing complexity of financial products, enlightened public policy goals to alleviate poverty, improve equity and enhance growth, as well as increasing global interconnectivity, have driven the regulators to beef up Shariah compliance surveillance. Punitive measures provided under this Act are designed to act as a deterrent to would-be Shariah non-compliance offenders; and at the stroke of a pen the new law has created a new breed of corporate criminals. The recently gazetted Islamic Financial Services Act 2013 (and its conventional counterpart the Financial Services Act 2013) is regarded by many as a “landmark law” for the multifaceted regulatory objectives it has to fulfil to ensure financial stability. This paper embarks on an impact analysis of the IFSA 2013 from the Shariah-compliance and governance-perspective to examine whether the new law has overcome the constraints or limitations of the Malaysian Shariah Governance Framework (SGF 2011) to ensure effective Shariah governance, as highlighted by the author’s earlier studies on Shariah audit and her critical appraisal of the Bank’s Shariah governance framework, the SGF 2011.2 Reference is made to the specific section, Part IV, on “Shariah Requirements” of the IFSA 2013, to see whether the prevailing concerns regarding the accountability, independence and objectivity of the SC have been given due consideration. It will also assess the adequacy of protection accorded to consumers through the expanded avenues for consumer redress as provided under this Act to strengthen the level of confidence in the Islamic financial system.